The Indian Girl who Dreams of America - Restiau, Christophe (France, 2015)
Manleen, a 30 year old Indian woman, returned to New Delhi to live with her parents following her divorce after an arranged marriage. Her mother would like her to remarry. She refuses and insists on remaining single in order to be able to continue her secret relationship with Sebastien, a French man. The girl leads a double life while she risks being banished from her family.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films